Supported Ionic Liquid‐Like Phases (SILLPs) as Immobilised Catalysts for the Multistep and Multicatalytic Continuous Flow Synthesis of Chiral Cyanohydrins. Issue 7 (5th March 2019) - Peris, Edgar; Porcar, Raúl; Burguete, María Isabel; García‐Verdugo, Eduardo; Luis, Santiago V.
Abstract: Supported Ionic Liquid‐Like Phases have been found to be efficient organocatalysts for the synthesis of cyanohydrin esters under solvent‐free conditions by an "electrophile‐nucleophile dual activation" based on hydrogen bond formation. The combination of multiple and consecutive multicatalytic steps in a single and integrated cascade process of organocatalytic SILLPs with commercially available supported Candida antarctica lipase type B (CAL‐B) has allowed developing an efficient process for the multicatalytic synthesis of enantiopure cyanohydrins under flow conditions. Abstract : Step it up : An integrated cascade multicatalytic multiple step flow process based on the appropriated combination of organocatalytic supported ionic liquid‐like phases (SILLPs) together with commercially available supported Candida antarctica lipase type B (CAL‐B) is reported for the efficient synthesis of enantiopure cyanohydrins.